Studies towards the total synthesis of (-)-lemonomycin - Chen, Yuyin, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2006)
An asymmetric synthesis of the tetracyclic core of (-)-lemonomycin is presented. It features an efficient route towards a highly versatile tetrahydroisoquinoline intermediate, in which a diastereoselective Pictet-Spengler reaction has been developed. In addition, a novel oxidation was discovered in the process of an azomethine ylide cyclization for construction of C and D rings of lemonomycin. An investigation into the mechanism of this novel oxidation has been carried out and the results discussed. The tetracyclic enamide from this process represents a highly functionalized and versatile intermediate. Interestingly, the enamide double bond proved very resistant to reduction and this transformation was fully investigated. More recently, with high-pressure hydrogenation equipment, promising leads towards hydrogenation of this enamide have been uncovered.
Keywords: Asymmetric synthesis; Antineoplastic antibiotics